THE LATEST TRENDS IN THE FORMATION OF THE ARCHITECTURE OF MODERN PUBLIC CENTERS IN A SUSTAINABLE DEVELOPMENT: Array - Dudka, O. (Municipal economy of cities. Series: «Economy science», 2020)
The article reveals the latest trends in the modern development of the architecture of public centers in large cities, innovative methods of formation in the urban environment, defines their specificity and requirements, analyzes the features, patterns and modern design solutions in conditions of sustainable development. The relevance of this study is associated with the need for new systemic approaches in the formation of multifunctional facilities, taking into account modern urban planning concepts, which allow the formation of new types of public entities and become an important structural element of the urban environment. Turning to foreign experience in organizing multifunctional public centers, one can find that the main components of the architectural formation are their urban planning and the spatial organization of a favorable architectural environment. It is important to note this aspect: for the formation of large public centers in conditions of sustainable development, the following main trends are characteristic: the formation of a developed spatial organization - an architectural and compositional formation. Also a bright architectural and artistic image - a dominant in the urban environment, integration into the natural landscape - ecological direction of sustainable development, effective functional zoning, well-developed engineering infrastructure and communications. Thus, it has been determined that a multifunctional public center in the structure of a large city is a specific type of architectural object, which is formed into a single complex of spatial and planning elements that organize the core of the social and business life of this city.